Children and adolescents' experiences of primary lymphoedema: semistructured interview study. Issue 7 (17th February 2018) - Hanson, Camilla S; Newsom, Johanna; Singh-Grewal, Davinder; Henschke, Nicholas; Patterson, Margaret; Tong, Allison
Abstract : Background: Congenital lymphoedema is a lifelong condition that has detrimental physical and psychosocial outcomes for young patients and burdensome treatment responsibilities that may hamper patients' motivation for self-management. There is limited research from the perspective of young people with primary lymphoedema. We aimed to describe the experiences and views of children and adolescents with lymphoedema to inform patient-centred practice. Methods: Twenty patients (aged 8–21 years) with primary lymphoedema were purposively sampled from two paediatric clinics in Sydney, Australia, to participate in a semistructured interview. The transcripts were analysed thematically. Results: We identified six themes: reinforcing abnormality (damaging self-esteem, self-consciousness, frustrating restrictions and isolation); negotiating uncertainties (fearing condition worsening, deprioritised and sidelined, questioning cause and permanence, widespread unawareness); vulnerability and caution (avoiding pain and discomfort, preventing severe and permanent consequences, depending on permission, limiting goals and aspirations); disruptive transition (resisting change, losing progress and support, avoiding treatment costs); developing resilience (focusing on the positives, embracing individuality, recalibrating normality, prioritising coping) and taking responsibility (individualising treatment, needing support, external pressure and motivation, sticking to a routine, seeking independence). Conclusion: Children and adolescents learn to adjust to the daily demands of lymphoedema management by individualising and accepting their treatment, but many continue to struggle with their self-esteem and lifestyle restrictions. Strategies are needed to empower young patients to advocate for themselves during their transition to adult care. Treatment plans that minimise social restrictions, address emotional consequences and incorporate patients' preferences could improve adherence, satisfaction and outcomes.